Classifit! : A toolbox for secondary school teachers to support implementation of physical activity in the classroom - Luttikhuizen, Van Gonneke (2018)
ABSTRACT Luttikhuizen, Gonneke van (2018). Classifit! A toolbox for secondary school teachers to support implementation of physical activity in the classroom. Master’s Thesis in Education. University of Jyväskylä. Department of Educa-tion.